Study of Diffractive Vector Meson Wave Functions: A Comparison of Boosted Gaussian and Gaussian LC Wave Function Profiles - Chalis Setyadi (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
In this work, we study the impact of using different vector meson wave functions on the cross-section of vector meson production in high energy diffractive scattering. We compare two commonly used vector meson wave functions, namely the boosted Gaussian and Gaus-LC. By applying these two wave functions to the diffractive vector meson production cross section, the total and differential cross sections are fitted with HERA data to obtain the best values of the free parameters. The results show that the application of different wave functions has no significant effect on the slope and amplitude of the cross-section. The differential cross section as a function of energy pattern, which tends to decrease more rapidly compared to the experimental data, is one of the features of the wave function that needs to be compensated by other components of a model to provide a good description of the data.